WTO casts a shadow over Nepal’s natural legacy - Roka, Krishna (Himalayan Journal of Sciences, 2006)
Can’t live with it, can’t live without it. Confused? The golden rule: Economic priorities should not be allowed to outweigh environmental imperativesHim J Sci 1(2): 72, 2003The full text is of this article is available at the Himalayan Journal of Sciences website